Analysis of the “Cognition” domain of the Individualized Music Therapy Assessment Profile (IMTAP) protocol (Per Musi, 2021)
Most assessment instruments in Music Therapy need to have their effectiveness proven, directing interventions in a manner consistent with the needs of individuals. Based on the relations inferred between musical language and written language, and studies on musical intervention in dyslexia, it could be hypothesized that children identified at risk of dyslexia could present some impairment in the “Cognition” domain of IMTAP, which evaluates the largest number of constructs similar to the items evaluated in psychological instruments. Therefore, this paper investigated whether a series of activities created to assess the “Cognition” domain of the IMTAP protocol was related to a battery encompassed by psychological instruments normally used in cognitive assessment of reading. The expectations of the study were not confirmed. Pearson's correlations, although significant, were very low, suggesting that the constructs evaluated by IMTAP are different from the constructs of the other tests used.